O poètike čelovečeskogo obŝeniâ - Dement’ev, Vadim V. (Stylistyka, 2021)
The article develops M.N. Kozhina’s ideas about the place of “artistic literary language” among functional styles. Esthetic meaning, esthetic evaluation and esthetic experience are understood as communicative phenomena here. Esthetically significant communicative senses are not the prerogative of written texts of belles-lettres. They are the part of the daily life, moreover, they are widely-accepted, well-recognized and necessary. The poetics of human communion is composed of speech acts in which the notional side is identified through complicated (or overcomplicated) organization and requires complicated interpretation, in which inferred senses are not limited to the lexical and grammatical meanings of the language units of which the speech act is composed. Esthetically significant oral dialogic communication may base itself upon senses produced by reading poetry or other pieces of fiction aloud. To the poetics of the human communion also belong language play, dramatized story-telling of the stories, picturesque means of the language employed in daily immediate communication. The poetics of the human communion is not, however, limited to these situations. It covers also situations of meetings, discussions, remarks, single words or even parts of words, intonation, silence, facial gestures which provoke deep deliberation, arouse admiration and nevertheless defy complete calculation and description and are usually lost in the structural language analysis. This phenomenon falls into one of the basic categories of the human language as the poetic function oflanguage which is identified through the correlation of the speech act to the same speech act itself is immanent in every situation of the language use. Every time the esthetically significant communication takes place senses are produced by the form of the speech act. Every time the esthetically significant oral communication takes place the priority also belongs to the form of the act of communication, but now to the communication on the whole: text and situation. By the form of the act of communication we understand all the significant components of the communicative situation including non-verbal ones (especially if the verbal part of the communication is insufficient). The position of M.M.Bakhtin is of principle importance to the author of this article: M.M.Bakhtin understood the attitudes between the speech acts of the immediate dialogue and speech acts of the characters in fiction as primary and secondary speech genres. Both secondary aesthetic speech genres and primary speech genres which have the common verbal nature are the object of aesthetic evaluation. The speech act theory correlates to the poetics of the human communion in the same way as the description of the grammar ofwritten language correlates to literally criticism. However, research of the poetics of human communion is by far more natural, logical and timely extension of the content-orientated trends of contemporary linguistics, than the poetics of written fiction is an extension of the traditional linguistics. Primary analysis of the esthetically significant oral dialogic speech is given in the article.